2016
DOI: 10.1155/2016/7124251
|View full text |Cite
|
Sign up to set email alerts
|

Punicalagin Induces Serum Low‐Density Lipoprotein Influx to Macrophages

Abstract: High levels of circulating low-density lipoprotein (LDL) are a primary initiating event in the development of atherosclerosis. Recently, the antiatherogenic effect of polyphenols has been shown to be exerted via a mechanism unrelated to their antioxidant capacity and to stem from their interaction with specific intracellular or plasma proteins. In this study, we investigated the interaction of the main polyphenol in pomegranate, punicalagin, with apolipoprotein B-100 (ApoB100) that surrounds LDL. Punicalagin b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…We have recently shown that punicalagin binds specifically to LDL and induces its influx into macrophage cells without foam cell formation. Such a mechanism may remove excess cholesterol from these cells to the liver, thereby lowering cholesterol levels in the circulation [ 39 ]. In this study, the antiatherogenic and anti-inflammatory properties of punicalagin and its ability to affect serum lipid and glucose levels were explored in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have recently shown that punicalagin binds specifically to LDL and induces its influx into macrophage cells without foam cell formation. Such a mechanism may remove excess cholesterol from these cells to the liver, thereby lowering cholesterol levels in the circulation [ 39 ]. In this study, the antiatherogenic and anti-inflammatory properties of punicalagin and its ability to affect serum lipid and glucose levels were explored in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, punicalagin, but not quercetin or other polyphenols, binds to LDL and induces its influx into macrophages without foam cell formation. This could be proposed as a mechanism that lowers cholesterol blood concentration and attenuates the development of atherosclerosis [ 39 ]. The present study is aimed at supporting this latter finding and to examine the biological functions of punicalagin and quercetin in relation to glucose and lipid levels, PON1 activity, and inflammation in the sera of hyperlipidemic mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was then replaced by the use of fluorescently labelled LDL proteins such as DiI-LDL, and subsequent immunostaining or extraction of protein for fluorescent readings using a spectrophotometer or plate reader 15,16 . Fluorescently labelled LDL has also been used in Fluorescence-activated cell sorting (FACS) for analysis of internalization of LDL and cell surface LDL binding 17 . While these methods allow for collection of data after treatment, monitoring the viability of the cells during treatment is not possible.…”
Section: Introduticonmentioning
confidence: 99%